Effect of Liquid Organic Fertilizer Type and Concentration on the Growth and Production of Purple Eggplant (Solanum melongena L.) - Agus Sulistyono; Kiki Adelia Putri; Djarwatiningsih Pongki S. (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
The productivity of purple eggplant has decreased and consumption continues to increase, it is necessary to increase the productivity of purple eggplant. Increasing productivity can be done by applying liquid organic fertilizer (LOF) derived from organic waste such as banana peels and fish waste. The purpose of this study was to determine the type and concentration of LOF that can help the growth and yield of purple eggplant. This research was conducted on the land of the Faculty of Agriculture, University of National Development (UPN) "Veteran" East Java in March to July 2022. The study used a factorial Randomized Block Design (RBD) consisting of 2 factors. The first factor was the LOF of banana peels and LOF of fish waste. The second factor is the LOF concentration level, namely 10%, 15%, 20%, 25% and 30%. The results showed that the treatment combination of fish waste LOF with a concentration of 30% gave plant with a biggest stem diameter of 1.01 cm. While the treatment combination of fish waste LOF with a concentration of 25% gave results with a total of 16.78 flowers and a total fruit weight of 1435.61 g/plant. Keywords:   Banana peels, Concentration, Eggplant, Fish waste, Yield